The reduction of melatonin levels is associated with the development of preeclampsia: a meta-analysis. (3rd April 2019) - Dou, Yuanyan; Lin, Binbin; Cheng, Hui; Wang, Changbao; Zhao, Mingming; Zhang, Jie; Wu, Jing
ABSTRACT: Objective : The aim of this analysis was to demonstrate the association between melatonin levels and the development of preeclampsia. Methods : Standardized mean difference (SMD) with 95% confidence interval (CI) was calculated using a random effects model. Results : The pooled SMD between case and control was 1.40 (95% CI: 0.26, 2.55; P = 0.02). And the pooled SMD between mild PE and severe PE was 5.25 (95% CI: 1.5, 9.01; P = 0.006). Conclusion : The meta-analysis illustrated that melatonin concentration was significantly lower in women with preeclampsia, and correlated with the severity of the disease.